Дети-мигранты: современные акценты научных исследований в России - Irina Simaeva (Problemy Wczesnej Edukacji)
The article provides an analysis of trends and approaches to researching foreign language learning problems, social and psychological adaptation, and the integration of migrant children in the multiethnic educational institutions of Russia. Showing new actual directions of scientific research: methodology of elementary education in foreign language of middle-school and older migrant children, learning, emotional expression of migrant children and development of their emotional intelligence. It indicates other necessary areas of international research and development in migrant children, a stable identification with the host country, and support for the psychological feeling of security to counter involvement in terrorism.